Outward FDI under China's Belt and Road Initiative: Between regulation and adaption - Maria Adele Carrai (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2020)
Chinese regulations and guidelines on the BRI's outward FDI increasingly align with international standards and best practices. However, this Perspective highlights that the voluntary nature of most of the guidelines and the Chinese central government's lack of control over its economic actors abroad makes China's approach adaptive to host countries.
Keywords: 330